Pengaruh Kebijakan Moneter terhadap Inflasi di Indonesia - Elisa Fitri Salsabila; Renanda Nurfatya; Siti Julaikah (Moneter : Jurnal Ekonomi dan Keuangan, 2024)
This study aims to describe the influence of money in circulation and the BI Rate on inflation in Indonesia from January 2021 to June 2023. This research is a literature study that departs from quantitative methods using secondary data obtained at the Central Statistics Agency (BPS). This research uses a multiple linear regression approach using SPSS data processing tools. The results of the F test show that simultaneously, the variable money in circulation and the BI rate have a significant effect on inflation in Indonesia. Partially, both also have a significant influence on inflation. The findings of this research underline the importance of continuing to create various policies to overcome the inflation problem in Indonesia.